Reengineering Evaluation Using Object Oriented Methodology - Kumar, Ashok; Sharma, Priti (Gyan Management Journal, 2009)
In the present changing world the present systems of recruitment process of police department ir facing new challenges. After reengineering accuracy and save manual powers. There are many sectors of our society where reengineering is showing it's remarkable. The model has been designed using object oriented methodolotrJ. This paper presents some advances towards the quantitative evaluation of design attributes can express the quality of internal structure. The study focused on the reengineering of the recruitment system of police department. An 00 design metrics set is reviewed, along with its rational. An experiment far collection and several suppositions regardi:ng the design. are evaluated. -In tltis paper the evaluation has been done using MOOD metrics.
Keywords: OOM (Object Oriented Methodology); MOOD (Metrics far Object Oriented design)